El Niño: Direkte und Fernwirkungen - Lozán, José L.; Graßl, Hartmut (Wissenschaftliche Auswertungen in Kooperation mit GEO Magazin, Hamburg, 2024)
El Niño: direct and long-distance effects - The direct effects of El Niño are found in the coastal areas of the tropical Pacific (Peru, Chile, northern Australia and south-east Asia). India is also affected by El Niño. Due to the drought, there is less moisture available for the monsoon rains. At high temperatures, monsoon rainfall (June-Sept) decreases significantly. Significant weather anomalies are also observed in the North Pacific, North America and the North Atlantic. In contrast to El Niño, La Niña causes an increase in the frequency of huricans in the tropical Atlantic. There are only a few regions in the world that remain unaffected by these weather events.